Mereka yang Tidak Dibayar Tinggi: Ibuisme, Taman Kanak-kanak, dan Kampung di Indramayu - Mochammad Arief Wicaksono (ETNOSIA : Jurnal Etnografi Indonesia, 2018)
The ideology of state-ibuism has always been interwoven with how the New Order regime until nowadays government constructing the “ideal” role of women in the family and community through the PKK (Pembinaan Kesejahteraan Keluarga) organization. However, in Cangkring Village, Indramayu, the ideology of ibuism works not because of the massive government regulating the role of women through the PKK organization, but it is possible because of the structure of the kampung community itself. Through involved observations and in-depth interviews about a kindergarten in the village, a group of housewives who dedicated themselves to teaching in kindergarten were met without getting paid high. From these socio-cultural phenomenons, this paper will describe descriptively and analytically that housewives in the Cangkring village are willing to become kindergarten teachers because of their moral burden as part of the warga kampung and also from community pressure from people who want their children to be able to read and write.